Leveraging digital marketing strategies to increase visitor engagement and sales for local tourism SME - Halim, Zulkifli; Sahri, Zulazeze; Sadjirin, Roslan; Canda, Roger; Ismail, Juhaida (International Journal of Accounting, Finance and Business, 2025)
Jengka Wonderland, located in Jengka Central City, is one of the first water theme parks between the Temerloh and Jerantut districts in the Maran district. This study aims to establish the online presence of Jengka Wonderland through the development of Local Tourism Digital Marketing Frameworks. The elements of the framework consist of a Business Website, Google Business Profile, Search Engine Optimization (SEO), and Google Ads that aim to provide a platform for marketing strategies and information dissemination through search engines to increase the number of visitors to the website thus boost up the ticket sales growth and strengthen the brand of Jengka Wonderland. The study obtains information on the number and characteristics of visitors, such as location, age, and gender, by providing a visitor tracking system on the website using Google products, which are Google Analytics and Google Search Console. The analysis shows that the number of visitors to Jengka Wonderland's website based on the target search keywords in the search engine after incorporating the framework has significantly increased.